Spondylidis, Spyros - (:unkn) unknown (My University, 2026)
Spyros Spondylidis is a PhD student in the Department of Marine Sciences, University of the Aegean. He received his Bachelor’s degree in Marine Sciences, University of the Aegean and his Master’s degree in Geography and Geoinformatics in the same University. Currently, he is writing his PhD thesis “Potential Fishing Zone detection with the use of Remote Sensing” and is an active researcher of the Marine Remote Sensing Group specializing in data analysis. He is skilled in Remote Sensing and GIS applications including, satellite imagery processing, classification, timeline analysis, ocean colour algorithm building, geo-spatial data analysis etc. His scientific interests involve mainly around applications of Remote Sensing in oceanography and in coastal environments and he is working with both satellite and UAS (Unmanned Aircraft System) data. He is knowledgeable in programming and automation and he focuses his research on near real time modeling and predictions. As an active scientist, he has been an author of scientific papers and he has participated in international scientific conferences as a presenter.